The Effectiveness of Active Range of Motion Exercises on the Pain Scale of Gouty Arthritis in the Elderly in the Working Area of the Gedong Tataan Health Center - Rifqi Perdana, Andhika; Sugiarto, Sugiarto; Hardono, Hardono; Sutrisno, Sutrisno (INDOGENIUS, 2025)
Background & Objective: Gouty arthritis is a condition that occurs when uric acid levels in the blood exceed normal limits, characterized by prolonged pain and impaired daily activities. Based on data at the Gedong Tataan Health Center, there were 26 elderly people with Gout Arthritis who experienced joint pain. Pain in patients with Gout Arthritis can be treated through pharmacological therapy, such as the administration of drugs, and non-pharmacological therapy, such as active range of motion exercises. This study aims to determine the effectiveness of active Range Of Motion exercises on the Gout Arthritis pain scale in the elderly in the Gedong Tataan Health Center Working Area. Method: Quantitative research method with quasy experiment type and pretest posttest control design approach. The population of this study was 26 elderly people while the sample used by the total sampling technique was divided into 2 groups, consisting of 13 intervention groups, and 13 control groups. The research instrument used SOP Range Of Motion and pain scale measurements, the data analysis test used in this study used Mann-Whitney. Result: The results of the study obtained a p-value of 0.004, meaning that there is an effectiveness of active Range Of Motion exercises on the Gout Arthritis pain scale in the elderly in the Gedong Tataan Health Center Working Area. Conclusion: It is hoped that this intervention can be applied at the health center in overcoming pain complaints in the elderly suffering from Gout Arthritis.